The Existence of Islamic Norms in the Indonesia Constitutional Court Decisions No.22/PUU-XV/2017 - Lindi Rohma Octavia; Rifqi Ridlo Phahlevy (Rechtsidee, 2020)
This study discusses the existence of Islamic norms in the Constitutional Court decisions. This study uses a case approach by examining the Constitutional Court decision no. 22 / PUU-XV / 2017. Data obtained from primary, secondary and tertiary data relating to legal issues in this paper. The main problem in this research is the consideration and decision of the Constitutional Court on the case decision No. 22 / PUU-XV / 2017 concerning marriage which is quite highlighted by the Indonesian people. What was tested in the a quo decision was article 7 paragraph (1) of Law No. 1 of 1974 concerning Marriage with article 27 paragraph (1) of the 1945 Constitution as a touchstone. In the a quo decision the petitioners argued that article 7 paragraph (1) was an article that was discriminatory for women. On the a quo decision, the panel of judges granted part of the petition's petition. the legal consequence of the Constitutional Court decision No. 22 / PUU-XV / 2017 is the emergence of Law No. 16 of 2019, amendments to Law No. 1 of 1974 concerning marriage